2002
DOI: 10.1542/peds.109.5.784
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Impairs Cerebral and Intestinal Blood Flow Velocity in Preterm Infants

Abstract: Oral administration of a high loading dose of caffeine results in marked reduction of cerebral and intestinal BFV, without changing LVO, blood pressure, and heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 25 publications
7
92
1
6
Order By: Relevance
“…Hoecker et al 4,6 examined the effect of caffeine loading in two regimens in two groups of 16 infants and showed no change in left ventricular CO (LVCO), HR or BP when measured 1 and 2 h after in one regimen and 1, 2 and 20 h later in the second regimen. Walther et al 5 showed an increase in LVCO and HR in 11 infants treated with aminophylline, however postaminophylline determinations were made 4 h after maintenance dose.…”
Section: Discussionmentioning
confidence: 99%
“…Hoecker et al 4,6 examined the effect of caffeine loading in two regimens in two groups of 16 infants and showed no change in left ventricular CO (LVCO), HR or BP when measured 1 and 2 h after in one regimen and 1, 2 and 20 h later in the second regimen. Walther et al 5 showed an increase in LVCO and HR in 11 infants treated with aminophylline, however postaminophylline determinations were made 4 h after maintenance dose.…”
Section: Discussionmentioning
confidence: 99%
“…NIRS and cranial ultrasound studies were performed within 24 h of birth and repeated at 48 and 72 h of life. NIRS and cerebral ultrasound were not performed within 2 h of clinical interventions that are known to alter cerebral oxygen supply and extraction, including administration of surfactant (36), indomethacin/ibuprofen (37), and caffeine (38).…”
Section: Cerebral Oxygen Delivery and Consumptionmentioning
confidence: 99%
“…[76][77][78] As a result of these findings there were concerns about the long-term effects of caffeine on brain development. However, results of placebo-controlled multicenter trials showed that caffeine therapy for AOP reduces the incidence of bronchopulmonary dysplasia 79 and improves survival without neurodevelopmental disability in very low birth weight infants.…”
Section: Treatment Strategiesmentioning
confidence: 99%